Clinical study of lenvatinib in the treatment of hepatitis virus-related hepatocellular carcinoma and antiviral therapy - Li, Xiaomi; Wang, Jingyan; Ding, Xiaoyan; Xu, Yawen; Yu, Minghua; Wu, Hongxiao; Deng, Na; Li, Wei; Chen, Jinglong (Frontiers in Pharmacology, 2023)
Background: Lenvatinib is recommended as a first-line tyrosine kinase inhibitor for advanced hepatocellular carcinoma (HCC) since 2017. The aim of this study was to compare the clinical action of lenvatinib in hepatitis B virus (HBV)-related HCC and hepatitis C virus (HCV)-related HCC. Methods: A continuous cohort of advanced HCC was retrospectively enrolled. And the patients were divided into HBV-related HCC and HCV-related HCC based on previous history of hepatitis virus infection. Then propensity score matching (PSM) was conducted to compare objective response rate (ORR),disease control rate (DCR),progression-free survival (PFS),overall survival (OS) and safety between the two groups. Results: A total of 203 eligible patients were included, with 72 HBV-related HCC and 36 HCV-related HCC after PSM. Both ORR (20.8% vs. 5.6%, P = .0759) and DCR (76.4% vs. 52.8%, P = .0232) were significantly higher in the HBV-related HCC than in the HCV-related HCC. Although no statistical differences in PFS (6.1 months vs. 3.3 months, P = .17) and OS (14.9 months vs. 17.7 months, P = .96) were observed between the two groups, there was a trend of difference in the PFS survival curve. On multivariate regression analysis of PFS, both HBV infection (HR, .54; 95% CI, .31–.95; P = .0332) and antiviral time >5 years (HR, .49; 95% CI, .26–.9; P = .0219) were identified as independent favorable factors, and AFP >200 ng/mL (HR, 1.88; 95% CI, 1.1–3.22; P = .0216) were found to be an independent adverse factor. In addition, compared with HCC who received the first dose of antiviral drugs less than 5 years, the patients who were administered those drugs over 5 years had a significantly favorable PFS (11.27 months vs. 3.87 months, P = .0011). Lenvatinib was well tolerated in all patients and the adverse events (AEs) were similar between the two groups. Conclusion: It seemed that lenvatinib benefited more in HBV-related advanced HCC in delaying disease progression, compared to those with HCV-related advanced HCC.